Clinical heterogeneity of progressive supranuclear palsy - Alexey A. Tappakhov; Tatiana E. Popova; Tatiana G. Govorova; Alyona Yu. Petrova (Анналы клинической и экспериментальной неврологии, 2018)
Progressive supranuclear palsy (PSP) is a sporadic neurodegenerative disease characterized by oculomotor disorders, early onset of postural instability and cognitive dysfunction. Classic form of the disease (Richardsons syndrome) develops only in 24% of all cases, while other phenotypes are registered in most patients. Clinical manifestations of the various types the PSP, as well as their similarities and differences with other nosological forms of extrapyramidal disorders are described in the current review. New diagnostic criteria of PSP developed by the International Society for the Parkinson's Disease and Movement Disorders in 2017 are discussed. Two clinical cases of PSP in patients of Yakhut ethnic origin are presented: in the first case there was classical variant of the disease (Richardsons syndrome), and in the second case a PSP-parkinsonism variant.